Roles of wildlife in epidemiology of rabies: A mini-review - Aiyedun, Julius Olaniyi; Oludairo, Oladapo Oyedeji; Olorunshola, Isaac Dayo (Journal of Advanced Veterinary and Animal Research, 2017)
The roles of wildlife in rabies transmission are still underestimated in many parts of the world. In the developed countries, epidemiology of rabies considering wildlife has been well documented. However, in the least developed and developing countries, emphasis has not given on this issue. Human population is increasing all over the world, and new localities are continuously developing. As a result, wildlife territory is decreasing, and the animals are coming in close contact with humans. Besides, many people are keeping wildlife as the sources of their pleasures. Due to the increased interaction among wildlife, domestic animals and human there is need to intensify efforts on mass education and building of awareness on the risks of rabies spreading by the wildlife, and to institute effective preventive measures to control over the disease. In this mini-review, roles of wildlife in epidemiology of rabies has been discussed considering the dynamics of wildlife in relation with associated intrinsic and extrinsic factors. http://doi.org/10.5455/javar.2017.d198 XML PubReader